2015
DOI: 10.1088/0029-5515/55/9/093033
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten ‘fuzz’ growth re-examined: the dependence on ion fluence in non-erosive and erosive helium plasma

Abstract: The thickness x, of tungsten fuzz layers are measured for non-varying helium (He) plasma exposure conditions spanning four orders of ion fluence Φ 10 24 − 10 28 m-2 and flux Γ 10 19 − 10 23 m-2 s-1 , at 1000−1140 K under low energy He ion impact (50 − 80) eV. The data obtained are complemented by previously published data of similar growth conditions, and collectively analysed. The new analysis allows for the reconciliation of fast high flux growth with commonly observed slower growth at lower flux. It is demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
115
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 38 publications
21
115
1
Order By: Relevance
“…1 (a) A schematic of the temporal evolution of the incident ion energy and SEM micrographs of the samples exposed to the He plasmas at T s of (b) 1100 and (c) 1300 K. The irradiation condition was as follows: E L = 7 -8 eV and Φ H = 1.5 -1.8 × 10 25 m −2 and D = 10 %. [7]. Recent comparison of the thickness of fuzz layer grown in the gaps of castellated W in PISCES-A between experiments and particle simulation have suggested the accuracy of the value [8].…”
Section: Pulsation Effects Of Incident Ion Energy On W Fuzz Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (a) A schematic of the temporal evolution of the incident ion energy and SEM micrographs of the samples exposed to the He plasmas at T s of (b) 1100 and (c) 1300 K. The irradiation condition was as follows: E L = 7 -8 eV and Φ H = 1.5 -1.8 × 10 25 m −2 and D = 10 %. [7]. Recent comparison of the thickness of fuzz layer grown in the gaps of castellated W in PISCES-A between experiments and particle simulation have suggested the accuracy of the value [8].…”
Section: Pulsation Effects Of Incident Ion Energy On W Fuzz Growthmentioning
confidence: 99%
“…where C is a coefficient; following fit values were obtained [7]: C = 2.36 (1) using a contribution factor α. The red dotted line in Fig.…”
Section: Pulsation Effects Of Incident Ion Energy On W Fuzz Growthmentioning
confidence: 99%
“…Figure 5 summarizes the relationship between the morphology changes and the irradiation conditions. When the surface temperature was lower than 1100 K and the flu-3406074-3 reported that the thickness of fuzz layer depended on square root of fluence, and the fluence had threshold, which was called incubation fluence, in order to form fuzz structure [18]. On W, nanostructures were formed on the entire surface at the fluence of ∼ 10 25 m −2 , which was about one order of magnitude lower than that of Pt [1,18]; also, the incubation fluence of Pt was likely to be about one order of magnitude higher than that of W.…”
Section: He Plasma Irradiation To Tungsten Carbidementioning
confidence: 99%
“…Recent experimental results reported in Ref. [42] indicate that fuzz growth following the square root dependence only starts after accumulating an incubation fluence. Although the experiments were carried out at different irradiation conditions (He ion energy, flux and temperature), the incubation fluence is qualitatively comparable to the simulation results presented in this Chapter.…”
Section: Resultsmentioning
confidence: 96%
“…In general, not only large He bubbles but also He trapped in few vacancies can cause microstructural changes [37,38], even at low energy. Indeed, void formation and underdense W nanostructures (so called "fuzz") have been observed in irradiation conditions similar to those that will have to face the divertor in MCF [39][40][41][42].…”
Section: Acknowledgementsmentioning
confidence: 99%